Impact of China’s new quality agricultural productive forces on carbon emissions from grain production and its mechanism - FAN Zhennan, QIN Zhaohui, DING Zhiguo, TAN Qijia (Ziyuan Kexue, 2025)
[Objective] Promoting low-carbon transformation of grain production is a key measure to ensure food security. Exploring the impact of new quality agricultural productive forces on carbon emissions in grain production can help to expand new avenues for ensuring the sustainable development of the grain system. [Methods] Based on the provincial panel data of China from 2011 to 2022, this study used the fixed effects model, mediation effect model, and threshold effect model to explore the impact of new quality agricultural productive forces on carbon emissions from grain production and its mechanism. [Results] (1) The new quality agricultural productive forces in China shows a continuous upward trend, and the overall regional differences are characterized by the main grain sales areas>main grain production areas>balanced production and sales areas. (2) There was a significant inhibitory effect of new quality agricultural productive forces on carbon emissions from grain production. (3) Mechanism analysis revealed that new quality agricultural productive forces mainly suppresses carbon emissions from grain production by expanding the scale of farmers’ operations. (4) Heterogeneity analysis showed that all three dimensions of new quality agricultural productive forces can reduce carbon emissions from grain production, and the carbon reduction effect was high for new agricultural workforce, followed by new agricultural means of production, and low for new agricultural objects of work; In terms of grain production functional areas and geographical locations, the carbon reduction effect of new quality agricultural productive forces mainly occurred in the main grain producing areas, production and sales balanced areas, and northern regions. (5) There was a single threshold in the process of new quality agricultural productive forces affecting carbon emissions from grain production. When the new quality agricultural productive forces exceeded the threshold value of 0.144, its inhibitory effect on carbon emissions in grain production is stronger than before the threshold. [Conclusion] The development of new quality agricultural productive forces helps to replace small-scale farmers with large-scale households, thereby reducing carbon emissions from grain production. We should actively cultivate new types of agricultural management entities, fully utilize intelligent green new technologies and modern agricultural machinery and equipment, develop moderate scale operations, and achieve organic integration with emerging industries related to agriculture in the future, so as to fully tap into the carbon reduction potential of new quality agricultural productive forces.